Implementation of project based learning by utilizing mangrove ecosystem to improve students creative thinking skills - A R Hidayat; A Munandar; W Surakusumah (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Project-based learning (PjBL) is an innovative approach in learning process. It was important strategies to achieve success in the 21st century. This study aimed to describe the influence PjBL models by leveraging the local potential of mangrove forests towards the improve the students creative thinking skills in ecosystem learning. Using quasi experimental method with nonequivalen pre-test post test control groups design. Research subject involved 34 students (with PjBL) and 37 students (direct learning) in SMAN 1 Parigi at the District of Pangandaran, West Java. The results show a significant difference in students' creative thinking skills between PjBL classes and direct learning (p-value = 0.000). The conclusion that PjBL influence on students' creative thinking skills so that can be used as an alternative model of learning for teachers in refining the process of biological learning to develop students creative thinking skills.